Experimental Study of Combustion Fluctuation Reduction Using In-Cylinder Pressure Estimation in Gasoline Engine - Mitsuhisa Ichiyanagi; Willyanto Anggono; Edyta Dzieminska; Takashi Suzuki (Institute of Research and Community Outreach - Petra Christian University, 2018)
Gasoline engines needs to reduce its negative emission waste and raise its thermal efficiency. Previous studies have shown an improvement of engines by regulating the ignition timing and retaining the engine at certain air-to-fuel ratio. Additional development of the thermal efficiency is anticipated by reducing the oscillation of pressure due to combustion (referred to as combustion fluctuation) during each cycle. Reducing the combustion fluctuations promotes the generation of a stable combustion field and improves fuel consumption. Since the combustion fluctuations are significantly affected by the in-cylinder pressure at compression top dead center (referred to as TDC pressure), the present study proposes a method to estimate the TDC pressure in the next cycle. The estimation was conducted by measuring the in-cylinder pressure at exhaust valve opening in the given cycle. This study also developed the method to reduce the combustion fluctuations by using the TDC pressure estimation and controlling the ignition timing. In our experiments, it was found that the developed methods reduced the fluctuations of the indicated mean effective pressure (IMEP), the maximum in-cylinder pressure, and the TDC pressure by 62.1%, 51.2%, and 38.5%, respectively.